Enhancing radar absorption performance of Sr-hexaferrite by hybridization with coiled carbon nanotubes via chemical vapour deposition method - Azis, Raba'ah Syahidah; Muhammad Zulkimi, Muhammad Misbah; Ismail, Ismayadi; Ertugrul, Mehmet; Hamidon, Mohd Nizar; Hasan, Intan Helina; Yesilbag, Yasar Ozkan; Tuzluca Yesilbag, Fatma Nur; Ozturk, Gokhan; Hasar, Ugur Cem; Mokhtar, Nurhidayaty (Elsevier, 2023)
A strategy of a highly feasible method to achieve a broad bandwidth of radar absorbing materials (RAM) is reported. Herein the magnetic Sr-hexaferrite were prepared using a conventional sintering process at 900 °C and later hybridized with coiled carbon nanotubes (CNT) via a chemical vapour deposition (CVD) method. X-ray diffraction (XRD) detected two phases of compounds after sintering which were 36 of SrFe2O4 and 64 of SrFe12O19. Two groupings of nanoparticle size showed no significant effect on reflection loss (RL) performance. Interestingly after hybridization of coiled CNT with the magnetic materials, the permittivity was increased tremendously hence enhancing the RL. Multiple relaxations of dielectric and eddy current losses were responsible for the enhancement. The RL was increased as the thickness was increased from 1 mm to 3 mm. 6 of coiled CNT/Sr-hexaferrite hybrid resulted in low RL of -19 dB with the broadest bandwidth of 3GHz over X-band frequency. The report is important for paving future work in obtaining a desired broad bandwidth RAM.